Religiosity as a protective factor against suicidal behaviour. (5th April 2016) - Burshtein, S.; Dohrenwend, B. P.; Levav, I.; Werbeloff, N.; Davidson, M.; Weiser, M.
Abstract : Objective: Data suggest that adherence to religious beliefs is associated with lower rates of suicide. A number of mediating factors have been hypothesized to explain this association, including enhanced social support, less substance abuse, and lower rates of psychopathology. Method: We utilized data from a two‐phase population‐based, epidemiological study of mental disorders among young Jewish Israel born in a 10‐year birth‐cohort conducted in the 1980s. This study included data on religiosity and suicidal behaviour. Twenty‐five years thereafter, mortality data were obtained from a national vital statistics registry. Results: Rates of suicidal ideation were similar among secular, partially observant, and religious subjects (9.4%, 6.7%, and 6.2%, respectively; adjusted OR for linear trend: 0.80, 95% CI: 0.58–1.09). Rates of suicide attempts were significantly lower among religious subjects (2.4%, 2.5%, and 0.4% for secular, partially observant, and religious, respectively; adjusted OR for linear trend: 0.62, 95% CI: 0.43–0.88). Of the 4914 subjects, eight died by suicide: Seven of them were secular and one was partially observant (χ 2 = 2.52, P = 0.09). There were no differences in social functioning or rates of psychopathology among the study groups. Conclusion: Religiosity has a protective effect against suicide attempts, which is independent of social functioning, psychopathology, and substance use.